The Role of Muslim Intellectuals in the Transformation of Islamic Education in Indonesia: An Analysis of Physical and Non-Physical Works - Syawaldi, Syawaldi; M, Iswantir (STIT Ahlussunnah Bukittinggi, 2025)
This study examines the contribution of Muslim scholars to the transformation of Islamic Education in Indonesia by highlighting two main forms of work: physical work in the form of establishing institutions, curricula, and infrastructure, as well as non-physical work in the form of ideas, methodologies, and educational ethics. Through a systematic literature review approach, this study found that the synergy between the institutional and intellectual dimensions built by figures such as KH. Ahmad Dahlan, KH. Hasyim Asy'ari, Nurcholish Madjid, Azyumardi Azra, Haedar Nashir, and Quraish Shihab became an important foundation for the renewal of Islamic Religious Education. Physical works provide an implementative space for strengthening the values of religious moderation and digital literacy, while non-physical works form a framework of ethics and rationality in modern Islamic learning. The results of the analysis show that the integration of moderation, digitalization, and Artificial Intelligence in Islamic Religious Education expands the function of religious education as a means of forming an inclusive and civilized society. However, methodological limitations in existing studies require a longitudinal and mixed methods approach to verify the causal relationship between intellectual ideas and the transformation of Islamic education. In practical terms, this study recommends strengthening empirical research on Islamic Religious Education, providing digital ethics training for educators, and promoting collaboration among universities in developing a values-based and technology-based Islamic curriculum.